2018
DOI: 10.1159/000491545
|View full text |Cite
|
Sign up to set email alerts
|

Factor X Deficiency Caused by Nonsecretory Myeloma Successfully Corrected with Bortezomib: A Case Report and Review of the Literature

Abstract: A 62-year-old female presenting with anemia and extensive hemorrhages is reported. Coagulation tests showed significantly prolonged prothrombin time (PT) and activated partial thromboplastin time. Decreased levels of clotting factor X activity were determined (5.4%). Bone marrow biopsy revealed neoplastic plasma cells. Serum and urine protein electrophoresis were both negative for monoclonal gammopathy, and both bone marrow and abdominal fat biopsies were negative for amyloid deposition. The patient was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The presence of factor X deficiency in myeloma without amyloidosis is a rare occurrence. We found three previously published cases describing this rare association [4,5,13]. Two cases described factor X deficiency with improvement after myeloma treatment [4,5].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The presence of factor X deficiency in myeloma without amyloidosis is a rare occurrence. We found three previously published cases describing this rare association [4,5,13]. Two cases described factor X deficiency with improvement after myeloma treatment [4,5].…”
Section: Discussionmentioning
confidence: 87%
“…We found three previously published cases describing this rare association [4,5,13]. Two cases described factor X deficiency with improvement after myeloma treatment [4,5]. Mufti M et al reported a 20-year-old myeloma patient who developed factor X inhibitor, although amyloidosis was suspected, the workup was negative [13].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation